Legal Problems Of Building On Waqf Land Belonging To Other People Based On Law Number 41 Of 2004 Concerning Waqf (Case Study Of Decision Number 21/PDT.G/2021/PN/BNA) - Shely Irla Noravisa (Eduvest - Journal of Universal Studies, 2024)
Legal Problems of Erecting Buildings on Waqf Land Owned by Others Based on Law Number 41 of 2004 concerning Waqf (Case Study of Decision Number 21/Pdt.G/2021/PN/BNA) Waqf land is a form of giving movable or immovable property for the benefit of worship and general welfare by Muslims. And the purpose of waqf procurement should not be changed in any form to deny the pledge of the waqf deed itself.  The normative research method is used in this study to study the social and moral values of the community about changes in the function of waqf land without permission from the waqf and the Indonesian waqf body. This research uses several data collection results from a collection of legislation, Government Regulations, books, doctrines, documents and various other secondary legal sources. The results of the study stated that: 1) in this case, the erection of buildings that should not be allowed was only decided to dismantle the fence because it had cost a considerable amount. 2) in the legal considerations of the judge in the decision of case Number 21/Pdt.G/2021/PN/Bna, it is not appropriate because it tends to lean towards the elements of justice and legal certainty so that the element of usefulness is ignored and denies the fulfillment of obligations contained in article 5 of Law Number 48 of 2009 concerning the power of judges